Penilaian Kinerja Berbasis Target pada Karyawan Sales: Antara Implementasi dan Realitas Lapangan - Aisyah Fajriah Mecca; Christian Wiradendi Wolor (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
This study aims to analyze the implementation of target-based performance appraisal for sales department employees at PT B, a pharmaceutical company in Indonesia. A qualitative method with a case study approach was employed, with data collected through observation, semi-structured interviews, and documentation involving three participants selected using purposive sampling. The findings reveal that PT B’s KPI-based performance appraisal system operates in a structured manner through three evaluation stages: weekly monitoring, end-of-month assessment, and annual KPI evaluation. Employees’ understanding of work targets is generally adequate; however, gaps exist in their comprehension of performance indicators. Key challenges include end-of-month target pressure, technical operational issues, fluctuating market conditions, and uneven dissemination of evaluation indicators to all sales employees.